2019
DOI: 10.1002/bmc.4699
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of early antibiotic use in pediatric patients with acute respiratory infections by high‐performance liquid chromatography

Abstract: In this study, we developed and validated two reliable high‐performance liquid chromatography (HPLC) methods for the qualitative detection of six oral β‐lactams, which are commonly used in pediatric patients with acute respiratory infections (ARIs). Two distinct reverse‐phase chromatographic separations of six β‐lactams were obtained. Four β‐lactams (cefadroxil, cephalexin, cefaclor and cefixime) in urine were separated using a gradient program with a mobile phase consisting of K2HPO4 buffer (20 mm, pH 2.8) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Regarding the chromatographic columns, other authors have reported C 8 and C 6 columns (Toi et al, 2020;Vercheval et al, 2018;Zhang et al, 2014). In addition, C 18 columns have been reported as well (Alberellos et al, 2015;Foord, 1976;Grupta & Stewart, 1986;Szlagowska et al, 2010).…”
Section: Methods Developmentmentioning
confidence: 87%
“…Regarding the chromatographic columns, other authors have reported C 8 and C 6 columns (Toi et al, 2020;Vercheval et al, 2018;Zhang et al, 2014). In addition, C 18 columns have been reported as well (Alberellos et al, 2015;Foord, 1976;Grupta & Stewart, 1986;Szlagowska et al, 2010).…”
Section: Methods Developmentmentioning
confidence: 87%
“…Antibiotic levels in urine were determined using validated in-house protocols, as described earlier [ 31 ]. The most frequently used antibiotics in the hospital and sold in the pharmacy of Children’s Hospital 1 are listed in S1 Table .…”
Section: Methodsmentioning
confidence: 99%